Changes in the Blood Viscosity in Patients With SARS-CoV-2 Infection - Al-kuraishy, Hayder M.; Al-Gareeb, Ali I.; Al-Hamash, Sadiq M.; Cavalu, Simona; El-Bouseary, Maisra M.; Sonbol, Fatma I.; Batiha, Gaber El-Saber (Frontiers in Medicine, 2022)
Coronavirus disease 2019 (COVID-19) is caused by a novel virus known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). SARS-CoV-2-induced hyperinflammation together with alteration of plasma proteins, erythrocyte deformability, and platelet activation, may affect blood viscosity. Thus, this review aimed to study the link between SARS-CoV-2 infection and alteration of blood viscosity in Covid-19 patients. In order to review findings related to hyperviscosity in COVID-19, we suggested a protocol for narrative review of related published COVID-19 articles. Hyperviscosity syndrome is developed in different hematological disorders including multiple myeloma, sickle cell anemia, Waldenstorm macroglobulinemia, polycythemia, and leukemia. In COVID-19, SARS-CoV-2 may affect erythrocyte morphology via binding of membrane cluster of differentiation 147 (CD147) receptors, and B and 3 proteins on the erythrocyte membrane. Variations in erythrocyte fragility and deformability with endothelial dysfunction and oxidative stress in SARS-CoV-2 infection may cause hyperviscosity syndrome in COVID-19. Of interest, hyperviscosity syndrome in COVID-19 may cause poor tissue perfusion, peripheral vascular resistance, and thrombosis. Most of the COVID-19 patients with a blood viscosity more than 3.5 cp may develop coagulation disorders. Of interest, hyperviscosity syndrome is more commonly developed in vaccine recipients who had formerly received the COVID-19 vaccine due to higher underlying immunoglobulin concentrations, and only infrequently in those who have not received the COVID-19 vaccine. Taken together, these observations are untimely too early to give a final connotation between COVID-19 vaccination and the risk for development of hyperviscosity syndrome, consequently prospective and retrospective studies are necessary in this regard.